Differences in motor skills of pupils aged 13 measured in 1970 and 1995 - Stojanović Darko; Stojanović Nikola; Stojanović Toplica (Glasnik Antropološkog Društva Srbije, 2013)
Body fat percentage is higher in relation to muscle in reduced physical activity, which significantly affects the level of motorabilities of students. The results of previously conducted research in the area of motor skills quickly become obsolete. During school age tracking students growth and development enables us to assess the regularity of the developmental period. By measuring the motor dimensions we come to some data about their development. If we want to get to the question of whether there is a change in the development of motor skills, it is necessary to compare their development with the development of students the same age measured more than twenty years. The aim of this study was to determine the difference of motor abilities of the pupils aged 13 years measured in 1970 and 1995 year. Measurement of motor skills are performed according to the methodology that was applied by Kurelić et al. (1975). Determination of differences was done by Difference test from the statistical package Statistica 8.0 for Windows, compared to the availabledata of means and standard deviations of respondents. The results of this research indicate that students which are measured in 1970 had better motor skills compared to students of the same age measured in 1995, except in test foot taping (MTAN).